Landscape and environmental drivers of plant health decline during an active invasion of Xylella fastidiosa Wells et al. in Mediterranean agroecosystems - Ricardo Enrique Hernández-Lambraño; Francisco José Ruiz-Gómez; Montserrat Vilà; Blanca B. Landa; Rocío Hernández-Clemente; María Fernández-Bravo; Enrique Quesada-Moraga; Concepción Olivares-Garcia; Pablo González-Moreno (NeoBiota, 2026)
Invasive plant pathogens, such as Xylella fastidiosa ( Xf ), pose a major threat to global agricultural and natural ecosystems, yet their impacts are rarely assessed across agro–natural interfaces where plant diversity, landscape structure and environmental stress interact. Here, we examine how Xf infection, environmental drivers and adjacent vegetation jointly shape Xf impacts in almond orchards embedded within a forest–agriculture mosaic. We conducted field surveys in 19 almond orchards within the Xf -demarcated area of Alicante (Spain), assessing crop and wild plant health, plant composition, pathogen occurrence and climatic, topographic and landscape variables. Using generalised linear mixed models (GLMMs) within a multi-model inference framework, we show that defoliation and branch dieback in almond trees were strongly associated with Xf infection, shrub cover, landscape configuration and drought-related climatic stress. Contrary to expectations, plant diversity at the forest–agriculture interface did not buffer Xf -related damage. Instead, higher abundance of potential Xf host species in adjacent vegetation was linked to increased defoliation in infected orchards, suggesting an indirect facilitation of disease dynamics, potentially via vector persistence rather than direct pathogen spillover. In adjacent natural vegetation, plant health was more strongly influenced by abiotic stress, particularly temperature and water availability, than by Xf infection itself. Overall, our results identify key environmental and biotic correlates of invasion impact and highlight the need for landscape-scale approaches integrating climate stress, host composition and vector ecology in the forest-agriculture interface to improve risk assessment and management of invasive polyphagous pathogens.